Ectopic Expression of a Maize Gene Is Induced by Composite Insertions Generated Through Alternative Transposition. Issue 4 (1st December 2020) - Su, Weijia; Zuo, Tao; Peterson, Thomas
Abstract: Transposable elements (TEs) are DNA sequences that can mobilize and proliferate throughout eukaryotic genomes. Previous studies have shown that in plant genomes, TEs can influence gene expression in various ways, such as inserting in introns or exons to alter transcript structure and content, and providing novel promoters and regulatory elements to generate new regulatory patterns. Furthermore, TEs can also regulate gene expression at the epigenetic level by modifying chromatin structure, changing DNA methylation status, and generating small RNAs. In this study, we demonstrated that Ac/ fractured Ac (fAc ) TEs are able to induce ectopic gene expression by duplicating and shuffling enhancer elements. Ac/fAc elements belong to the hAT family of class II TEs. They can undergo standard transposition events, which involve the two termini of a single transposon, or alternative transposition events that involve the termini of two different nearby elements. Our previous studies have shown that alternative transposition can generate various genome rearrangements such as deletions, duplications, inversions, translocations, and composite insertions (CIs). We identified >50 independent cases of CIs generated by Ac/fAc alternative transposition and analyzed 10 of them in detail. We show that these CIs induced ectopic expression of the maize pericarp color 2 ( p2 ) gene, which encodes a Myb-related protein. All the CIs analyzed contain sequences including a transcriptional enhancer derived from the nearby p1 gene, suggesting that the CI-induced activation of p2 is affected by mobilization of the p1 enhancer. This is further supported by analysis of a mutant in which the CI is excised and p2 expression is lost. These results show that alternative transposition events are not only able to induce genome rearrangements, but also generate CIs that can control gene expression.